Elementary Teachers' Perceptions of a Comprehensive, Integrated, Three-Tiered Model of Prevention. (August 2021) - Menzies, Holly M.; Oakes, Wendy Peia; Lane, Kathleen Lynne; Royer, David James; Cantwell, Emily D.; Common, Eric Alan; Buckman, Mark
This study examined perceptions of teachers who implemented a tiered system of support, the comprehensive, integrated, three-tiered (Ci3T) model of prevention. We reported findings of four focus groups with a total of 18 elementary teachers who implemented Ci3T for 2 years. While the Ci3T model comprised elements addressing academics, behavior, and social-emotional learning, teachers were predominately concerned with issues related to students' behavior. Teachers reported difficulty moving from reactive to proactive classroom management approaches theoretically grounded in behavioral principles.